2015
DOI: 10.1007/s11306-015-0816-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals anomalous energy metabolism and oxidative stress pathways in chronic fatigue syndrome patients

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a debilitating long-term multisystem disorder with a central and inexplicably persistent fatigue symptom that is unable to be relieved by rest. Energy metabolism and oxidative stress have been recent focal points of ME/CFS research and in this study we were able to elucidate metabolic pathways that were indicative of their dysfunction. Blood and urine samples were collected from 34 females with ME/CFS (34.9 ± 1.8 SE years old) and 25 non-ME/CFS fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
181
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(200 citation statements)
references
References 43 publications
15
181
3
1
Order By: Relevance
“…Furthermore, the translocation of these enteric lactic acid products into the bloodstream could contribute to the elevated lactate reported in the cerebrospinal fluid of ME/CFS patients [138][139][140] and in the blood of a subgroup of patients [141]. This contrasts with reports of reduced blood lactate as measured by H-NMR metabolomics [39], which suggests that lactic acidosis may only affect a subgroup of patients. If IBS comorbidity accompanied by gut dysbiosis and hyperpermeability is indeed a subtype of ME/CFS, translocation of lactic acid produced by abnormally enriched Gram positive enteric bacteria in the affected individuals, rather than excessive production by host metabolism could explain this inconsistency.…”
Section: The Gut Microbiota and Metabolismmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the translocation of these enteric lactic acid products into the bloodstream could contribute to the elevated lactate reported in the cerebrospinal fluid of ME/CFS patients [138][139][140] and in the blood of a subgroup of patients [141]. This contrasts with reports of reduced blood lactate as measured by H-NMR metabolomics [39], which suggests that lactic acidosis may only affect a subgroup of patients. If IBS comorbidity accompanied by gut dysbiosis and hyperpermeability is indeed a subtype of ME/CFS, translocation of lactic acid produced by abnormally enriched Gram positive enteric bacteria in the affected individuals, rather than excessive production by host metabolism could explain this inconsistency.…”
Section: The Gut Microbiota and Metabolismmentioning
confidence: 88%
“…A subsequent study utilizing MS conversely reported an elevation in ornithine concentration with a decrease in citrulline, but this also suggests urea cycle dysregulation [6]. Subsequent work undertaken by the authors of the first study proposed that impaired glycolytic formation of pyruvate could be providing less downstream, oxidized pyruvate derivatives to be used as substrate for the tricarboxylic acid (TCA) cycle [39]. Work by others suggested that instead of a reduction in the glycolytic pyruvate supply, a deficiency in pyruvate dehydrogenase (PDH) function may form a bottleneck for the provision of TCA cycle substrate [40].…”
Section: Dysregulated Amino Acid Metabolism and Impaired Provision Ofmentioning
confidence: 99%
“…Finally, multiple gene sets regulated by INMEST involved cellular energy metabolism, which is curious given that fatigue is the cardinal symptom of ME and linked to alterations in cellular metabolism (39). The GO: Negative regulation of cellular carbohydrate metabolism is affected by INMEST with genes like GCK encoding the glucose sensor Glucokinase, which shifts cellular metabolism based on the availability of glucose (40) and was found in this cohort to be repressed in ME-patients after INMEST treatment ( Fig.…”
Section: Transcriptional Programs Altered In Me Patients Treated By Imentioning
confidence: 88%
“…Indeed, Michael et al reported that citrate-containing A(-)D also might contribute to improving fatigue in hemodialysis patients [22]. Comprehensive metabolomic analyses of plasma from chronic fatigue syndrome have demonstrated that citrate was preferentially decreased, which suggested deficiencies in adenosine triphosphate production secondary to dysregulation of the flow from pyruvate to citrate via acetyl CoA and that dysfunctional energy metabolism through the citric acid cycle is a fatigue phenotype [23]. We previously reported that fatigue can be an important predictor for cardiovascular events in hemodialysis patients independent of their nutritional or inflammatory status [6].…”
Section: St A(+)d 1st A(-)d After 2 Weeks Of A(+)d 7th A(-)d Aftermentioning
confidence: 99%